The metabolism of 11β-hydroxyandrostenedione by steroidogenic enzymes yields metabolites contributing to the androgen pool in prostate cancer - Du Toit, Therina (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.